2020
DOI: 10.1186/s13673-020-00227-9
|View full text |Cite
|
Sign up to set email alerts
|

An anonymous authenticated key-agreement scheme for multi-server infrastructure

Abstract: Due to single-time registration, the multi-server authentication provides benefit for getting services from different servers through trusted agent. Generally, users feel hesitation for registering themselves individually with all service providers due to the problem of memorizing the multiple passwords. The multi-server authentication allows a quick access to services by real-time customer validation on public channel. Thereafter, hundreds of multi-server authentication protocols have been introduced. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…However, we found that this AKE device is vulnerable to a temporary secret attack [ 20 ]. M. Akram et al [ 32 ] enhanced the security features by proposing an anonymous three-factor authentication scheme for multi-servers. The scheme designed was based on the elliptic curve cryptography, and the biometric information is verified by the user and the server separately.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…However, we found that this AKE device is vulnerable to a temporary secret attack [ 20 ]. M. Akram et al [ 32 ] enhanced the security features by proposing an anonymous three-factor authentication scheme for multi-servers. The scheme designed was based on the elliptic curve cryptography, and the biometric information is verified by the user and the server separately.…”
Section: Related Workmentioning
confidence: 99%
“…Here, we explain the comparison of the communication cost and the computation cost of the proposed scheme with other existing schemes [ 20 , 26 , 31 , 32 ] which are shown in Table 5 . The performance metrics can be explained as follows.…”
Section: Security Features Comparisonmentioning
confidence: 99%
See 2 more Smart Citations
“…To discover the private key of any node, an attacker must compromise all nodes involved in the threshold PKG. Notice that many other key management schemes were proposed in the literature, one can cite 85 …”
Section: Related Workmentioning
confidence: 99%